Inhibitory effects of Raphanus sativus root extracts on MUC5AC gene expression in human airway epithelial cells - Lu, Jia-Yin; Kuo, Ping-Chung; Li, Yue-Chiun; Chen, Wen-Yin; Hsu, Wei-Li; Tsai, Ching-Hsiu (NPJ science of food, 2025)
The root of Raphanus sativus (radish) is recognized for its bioactive compounds with anti-inflammatory, anti-tumor, and muscle spasm-inhibiting properties. This study explores the effects of different radish extracts on the overexpression of the MUC5AC gene, induced by phorbol 12-myristate 13-acetate (PMA), in human airway epithelial cells (NCI-H292). Our results showed that both methanol and ethyl acetate extracts significantly reduced PMA-induced mucus secretion, as confirmed by PAS staining. qPCR analysis revealed that the ethyl acetate extracts from dried and aged radish were more effective in regulating MUC5AC mucin gene expression. From the ethyl acetate extract of dried radish, four compounds were isolated: 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (compound 1), 5-(Hydroxymethyl) furfural (5-HMF, compound 2), 2-(2-formyl-5-(hydroxymethyl)-1H-pyrrol-1-yl) propanoic acid (compound 3), and 4-[formyl-5-(methoxymethyl)-1H-pyrrol-1-yl] butanoic acid (compound 4). This study marks the first isolation of these compounds from R. sativus root. Among these, 4-[formyl-5-(methoxymethyl)-1H-pyrrol-1-yl] butanoic acid exhibited the strongest regulatory activity on MUC5AC gene expression, highlighting its potential as a drug or mucus-related conditions.